The Carrier’s Liability for Passengers Injured in A Ship Fire on the Merak–Bakauheni Route - Maria Victoria Nandaswa; Amad Sudiro (Universitas Islam Negeri Alauddin Makassar, 2026)
This study examines the legal responsibility of carriers in maritime passenger transportation accidents, specifically analyzing the fire incident on KMP Royce 1 vessel operating on the Merak–Bakauheni route. The background of this research stems from the legal uncertainty surrounding carrier liability and compensation mechanisms for passengers in Indonesian maritime transportation, particularly when accidents occur causing casualties and material losses. The primary issues addressed are: first, how Act Number 17 of 2008 on Shipping regulates carrier responsibilities for passenger safety; second, what compensation mechanisms are available to victims of maritime accidents; and third, why analogical application of aviation regulations becomes necessary in maritime cases. The research objective is to analyze the adequacy of existing legal frameworks governing carrier liability in maritime passenger transportation and to identify regulatory gaps that necessitate analogical application of other transportation mode regulations. This study employs normative juridical research methods, utilizing statutory, case, and conceptual approaches. Legal materials were collected through library research and analyzed using deductive reasoning to examine the alignment between legal norms and their implementation. The findings reveal that Articles 40 and 41 of Act Number 17 of 2008 establish fundamental obligations for shipping companies to ensure passenger safety and provide compensation during accidents. However, the absence of specific implementing regulations for maritime passenger compensation has led to the analogical application of Minister of Transportation Regulation Number 77 of 2011, which originally governs air transportation. In the KMP Royce 1 case, the carrier's responsibilities encompassed passenger evacuation, medical treatment for injured victims, and compensation facilitation through PT Jasa Raharja. The study concludes that the regulatory vacuum in maritime passenger compensation creates legal uncertainty and inadequate protection for passengers. The implications suggest urgent need for comprehensive and specific regulations governing carrier liability and compensation mechanisms in maritime transportation to ensure legal certainty and optimal passenger protection.